Assessing risk of future cardiovascular events, healthcare resource utilization and costs in patients with type 2 diabetes, prior cardiovascular disease and both. (1st December 2020) - Nguyen, Chi; Luthra, Rakesh; Kuti, Effie; Willey, Vincent J.
Abstract: Background: Description of risk of cardiovascular (CV) events associated with diabetes is evolving. This US-based real-world study estimated risk of future CV events and heart failure (HF) from type 2 diabetes (T2DM) only, prior CV events only or T2DM plus prior CV events, versus controls, and evaluated healthcare resource utilization (HCRU) and costs. Methods and materials: This retrospective cohort study queried claims and mortality data for 638, 301 patients: T2DM only (377, 205); prior CV events only (130, 964); both T2DM and prior CV events (130, 132); and matched (1:1) controls, during 1 January 2012–31 December 2012. Cardiovascular diagnoses/events and death were assessed individually, and as composite endpoint (myocardial infarction [MI], stroke, transient ischemic attack [TIA], peripheral artery disease [PAD]), during follow-up, ending 31 July 2018. Results: Adjusting for age and gender, patients with T2DM only were 1.6, prior CV events only 2.5 and T2DM plus prior CV events 3.8 times likelier to have primary composite CV events relative to controls, p < .001. HF development was elevated across all three cohorts. Adjusted results showed inpatient admissions for T2DM only, CV events only and T2DM plus prior CV events were 1.37, 2.76 and 3.63 times greater than controls, respectively. All-cause healthcare costs were highest in the T2DM plus prior CV events cohort (2783 per patient per month [PPPM]) followed by the prior CV events only (1910 PPPM) and T2DM only cohorts (1343 PPPM), and controls (825 PPPM). Adjusted all-cause total costs were 1.48 for T2DM only, 1.49 for prior CV events only and 1.93 for T2DM plus prior CV events times higher compared to controls. Conclusion: In this large and geographically broad US based cohort, CV risk for T2DM patients was elevated, as was the risk for patients with prior CV events, while patients with T2DM plus prior CV events had the highest risk of future CV events. The substantial clinical and economic burden of CV events and HF in patients with both T2DM and prior CV events suggest a need for an integrated treatment and targeted intervention across both conditions.